Capacidade combinatória, diversidade genética e correlações em soja - Teixeira, Morganna Aparecida Justino (2021)
The choice of genitors for the formation of segregating populations in crosses is an extremely important step for breeding programs. The estimation of genetic components allows the identification of favorable hybrid combinations and, consequently, the obtaining of superior populations. Thus, the objective of this study was to estimate the general combining ability (GCA) and specific combining ability (SCA) of four parents in order to verify more favorable hybrid combinations for obtaining populations for selection of promising progenies for grain production and agronomic characters of importance. The experiment was carried out in a greenhouse of the Soybean Breeding Program, at Capim Branco farm of the Federal University of Uberlândia. For diallel analysis, four parents were adopted (BRS 263, TMG 4185, TMG 803 and UFUS Guará) and their six F1 hybrids were evaluated in a randomized complete block design with four replications. Each plot consisted of a pot cultivated with two plants. The following characters were evaluated: number of days to flowering and to maturity, plant height at flowering and at maturity, number of nodes at flowering and at maturity, height of first pod insertion, number of pods with one, two and three grains, total number of pods per plant, number of grains per pod and grain yield per plant. The genetic-statistical analysis was carried out using the Griffing methodology (1956), method 2. The parent UFUS Guará has favorable alleles for reducing the number of days to maturation, which can be indicated for crosses aiming at reducing the cycle. Parents UFUS Guará and BRS 263 are prominent in breeding programs aimed at raising production components. The combinations UFUS Guará X BRS 263 and UFUS Guará x TMG 4185 showed potential for decreasing the cycle and increasing grain production by plants, showing the capacity for the development of promising segregating populations.The chapter three of this study consisted of evaluating the genetic dissimilarity between advanced soybean lines in two cropping season, using agronomic characters using multivariate techniques; to determine the importance of characters in the genetic divergence of soybean and to estimate the genotypic and phenotypic correlations between the evaluated characters. The experiments were carried out in the experimental field located at Capim Branco Farm, in Uberlândia-MG, in the 2018/2019 and 2019/2020 seasons. 27 soybean genotypes were evaluated, 26 lines developed by the genetic breeding program of the Federal University of Uberlândia and one cultivar (BRSGO 7560). The design adopted was a randomized complete block with three replications. 14 agronomic traits were evaluated. The genotypes were grouped by the Scott-Knott test at the level of 5% probability. The genetic dissimilarity was estimated by the generalized Mahalanobis distance and the genotypes grouped by the UPGMA, Tocher methods and canonical variables. The presence of genetic variability was verified by the F test at 1 and 5% probability for all characters analyzed. The measures of dissimilarity showed high magnitude, ranging from 5 to 553 (harvest 2018/2019) and 9 and 455 (harvest 2019/2020). The greatest divergences found were, between the genotypes UFUS 5 and UFUS 27 and UFUS 2 and UFUS 27, in the 2018/2019 and 2019/2020 harvests, respectively. For the 2018/2019 crop, the character that most contributed to the genetic divergence between the genotypes was the number of days to maturity, while for the 2019/2020 crop the largest relative contribution was attributed to the character number of total pods. The comparative analysis between the methods of hierarchical grouping, optimization and canonical variables partially agreed in relation to the number of groups formed, coinciding by differentiating the UFUS 27 as the most distant from the other genotypes. Crossing the UFUS 27 line with the UFUS 5, UFUS 17, UFUS 18 and UFUS 25 genotypes are promising for cycle reduction and productivity. For both harvests, the genotypic correlations showed a higher magnitude than the phenotypic ones. There was a high magnitude correlation in NVT and PG, indicating a favorable effect of this character in relation to grain production.